Let's say Tom has T silver dollars, and Jimi has J silver dollars.
If tom has 7 more dollars than Jimi, then we can express it as follows:
![T=J+7](https://img.qammunity.org/2023/formulas/mathematics/college/pptmb231ah1ozoewuzpsob1m9nen980kav.png)
The total amount they both have is 77, then, it can be expressed as follows:
![T+J=71](https://img.qammunity.org/2023/formulas/mathematics/college/1hh6lunfnoihia3yutc88v2wiufppddkip.png)
Now we have a system of two equations and two unknowns.
An easy way to solve this is replacing the first equation in the second:
![J+7+J=71](https://img.qammunity.org/2023/formulas/mathematics/college/hapa5vh9zpr01vod9dcjk7uowa15q498bz.png)
Then, operating:
![2J+7=71](https://img.qammunity.org/2023/formulas/mathematics/college/os5qkj481qrp8dgblgbt996klx7ipirb52.png)
Now, solving for J:
![\begin{gathered} 2J=71-7 \\ 2J=64 \\ J=(64)/(2) \\ J=32 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/p7zzsusge2xe43fqfahk66ponj1okst5ji.png)
Now we have found how many silver dollars Jimi has. We can now use again the first equation we stated, replacing 32 where we have J:
![\begin{gathered} T=J+7 \\ T=32+7 \\ T=39 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/txfeg3a0yj15kvmbiw8j05bmnccbwf1c0v.png)
Then, Tom has 39 silver dollars.
We can prove this because 39 is 7 more than 32, and 39 + 32 = 71